An Intercomparison of VLF and Sounding Rocket Techniques for Measuring the Daytime D Region Ionosphere: Theoretical Implications. Issue 10 (13th October 2018) - Siskind, D. E.; Zawdie, K. A.; Sassi, F.; Drob, D. P.; Friedrich, M.
Abstract: We compare the two approaches that have been used to measure the lowermost ionosphere, the measurement of the propagation of very low frequency (VLF) radio waves and the in situ sampling by sounding rockets. We focus on the altitude, latitude, and zenith angle variation of the electron density profiles inferred from these two observational techniques as compared with a theoretical photochemical model. Our results show that below 68–70 km, the VLF data and the model agree better with each other than with the sounding rocket profile. At the lowest altitudes, near 60 km, both the VLF data and the model show a greater electron density at higher latitudes, consistent with a cosmic ray flux that increases with latitude, whereas the limited rocket data show a maximum at the tropics. Above 68–70 km, the VLF data and the sounding rockets agree better and at tropical latitudes, the model fails to reproduce the observations. Specifically, the calculated electron density is lower than the data by up to a factor of 2. Possible reasons for the model deficit include underestimates of the solar Lyman alpha flux, the solar X‐ray flux and the mesospheric nitric oxide density. Once these three factors are mitigated, the model is in agreement with the observations between 60 and 80 km. Plain Language Summary: Over the past 50–60 years, there have been two approaches toward measuring the lowermost ionosphere (below 90 km), the D region. One is by modeling the propagation of VLF radio waves; the other is by in situ sampling via rockets. Until now, these techniques have not been rigorously intercompared. By comparing both with each other and with a theoretical photochemical model, we show how they are complementary. The very low frequency data are most accurate below 70 km, while the rocket data are more accurate above 70 km. The photochemical model can be made to agree with these data provided certain assumptions are made about the solar Lyman alpha flux, solar X‐rays, and mesospheric nitric oxide (NO). Key Points: We compare two independent techniques for measuring the D region ionosphere Modeling VLF radio waves is most accurate below 70 km, in situ rockets are most accurate above 70 km Photochemical model can agree with observations, but there are uncertainties concerning neutral atmosphere and solar flux inputs